In vitro UV absorption properties and radical scavenging capacity of Morella parvifolia (Benth.) Parra-Os. extracts - Miguel Angel Puertas-Mejía; María Isabel Gutierrez-Villegas; Juan Camilo Mejía-Giraldo; Robert Winkler; Benjamín Rojano (Universidade de São Paulo, 2018)
The goal of this research was to identify major compounds of the aerial parts of M. parvifolia (Benth.) Parra-Os., that could enhance its possible application as additive in dermocosmetic products, as well as evaluate the antioxidant properties. The extracts agreed with the broad-spectrum UVB/UVA absorption detected and could act as broad-spectrum sunscreens, covering the UVA and UVB range. Methanolic extracts showed an important antiradical capacity (0.46 and 0.47 g/µmol DPPH), TPC (37.58 and 51.41mg GAE/g DS) and TAC (1.12 and 3.31 mg C3GE/g DS) in fruits and leaves, respectively. M. parvifolia could be considered as a prospective source of natural UV-radiation absorbers with antioxidant capacity. Although the results have clearly demonstrated the potential photoprotection capacity, more studies are needed to enhance its application as an additive in pharmaceutical and medicinal formulations.